A sequential case series of 23 intubations in a rural emergency department in New Zealand. (10th August 2017) - Powell, Eleanor; Alkhouri, Hatem; McCarthy, Sally; Mackenzie, John; Fogg, Toby; Vassiliadis, John; Cresswell, Chris
Abstract: Objective: To describe the practice and procedure of emergency intubation in Whanganui Emergency Department, New Zealand and determine whether intubation can be carried out effectively in the rural setting. Method: A prospective observational study using the Australia and New Zealand Airway Registry proforma to collect data on the indication, lead intubator, first‐pass success rate and peri‐procedural complications. Data were also collected on whether a formal airway assessment was carried out and whether a checklist was used. Results: Twenty‐three patients were intubated in the emergency department over a 12‐month period. Sixty‐two percent (14/23 cases) were medical encounters and the remaining 38% of indications due to a trauma. Head injury was the most common indication (23%). Ninety‐two percent of primary intubators were emergency department‐based Fellowship of the Australasian College for Emergency Medicine or resident medical officers, while anaesthetic‐trained operators accounted for just 8%. Our first‐pass intubation success rate was 87% and 16% of cases had procedural complications. Sixty‐five percent (15/23) carried out a formal airway assessment and a checklist was only used in 23% of cases. Conclusion: This sequential case series is the first study looking at airway management in rural New Zealand emergency department airway practice. Overall intubation success rates were comparable to larger tertiary centres across Australasia. We have demonstrated that with adequate resources and adherence to interventions, a rural emergency department can provide effective airway management.